Penang's history, my story - Wong, Chun Wai (Star Publications (Malaysia) Bhd, 2014)
The latest book by Wong Chun Wai takes us through a journey of the streets of Penang. History comes alive as Wong shares his personal stories growing up in his beloved hometown. The book sheds light on facets of Penang's history that are not known to many. Compiled from the series he wrote for the Metro section of The Star, the book also comes with the bonus sharing by Chun Wai's friends who also come from Penang. This book is a must-read not only for Penangites but for all Malaysians who treasure the need to keep history alive